The influence of social comparison on quarter life crisis mediated by psychological well-being in emerging adults - Fifit Wahyuni; Siska Adinda Prabowo Putri; I Rheny Arum Permitasari (University of Merdeka Malang, 2025)
In early adulthood, individuals experience significant life transitions, which can lead to difficulties in self-adjustment due to societal expectations, commonly manifested in the phenomenon known as the quarter-life crisis. This condition is often triggered by social comparison. One potential factor that may help mitigate the emergence of a quarter-life crisis in early adulthood is psychological well-being. This study aims to examine and analyze the role of psychological well-being as a mediator between social comparison and the quarter-life crisis in early adulthood. The sampling technique used was nonprobability sampling, with criteria including individuals aged 18–40 years and residing in the city of Semarang, resulting in a total of 384 respondents. Data analysis was conducted using path analysis with the assistance of SPSS. The results showed a Sobel test value of 6.39 and a significance level of 0.000, indicating that psychological well-being serves as a mediator between social comparison and the quarter-life crisis in early adulthood. The implication of these findings is that enhancing psychological well-being can reduce the negative impact of social comparison on the level of quarter-life crisis. Therefore, interventions focusing on improving psychological well-being can serve as an effective strategy in addressing this crisis.